Phytogeography of the bryophyte floras of oak forests and páramo of the Cordillera de Talamanca, Costa Rica - Ingo Holz; S. Robbert Gradstein (Journal of Biogeography, 2005)
Aim Central America is a biogeographically interesting area because of its location between the rich and very different biota of North and South America. We aim to assess phytogeographical patterns in the bryophyte floras of oak forests and páramo of the Cordillera de Talamanca, Costa Rica. Location Tropical America, in particular the montane area of Cordillera de Talamanca, Costa Rica. Methods The analysis is based on a new critical inventory of the montane bryophyte flora of Cordillera de Talamanca. All species were assigned to phytogeographical elements on the basis of their currently known distribution. Absolute and percentage similarities were employed to evaluate floristic affinities. Results A total of 401 species [191 hepatics (liverworts), one hornwort, 209 mosses] are recorded; of these, 251 species (128 hepatics, one hornwort, 122 mosses) occur in oak forests. Ninety‐three per cent of all oak forest species are tropical in distribution, the remaining 7% are temperate (4%) and cosmopolitan (3%) species. The neotropical element includes almost 74% of the species, the wide tropical element (pantropical, amphi‐atlantic, amphi‐pacific) only 19%. A significant part of the neotropical species from oak forests are species with tropical Andean‐centred ranges (27%). As compared with bryophyte species, vascular plant genera in the study region are represented by fewer neotropical, more temperate and more amphi‐pacific taxa. Bryophyte floras of different microhabitats within the oak forest and epiphytic bryophyte floras on Quercus copeyensis in primary, early secondary and late secondary oak forest show a similar phytogeographical make‐up to the total oak forest bryophyte flora. Comparison of oak forest and páramo reveals a greater affinity of the páramo bryophyte flora to temperate regions and the great importance of the páramo element in páramo. Surprisingly, oak forests have more Central American endemics than páramo. Main conclusions (1) Providing first insights into the phytogeographical patterns of the bryophyte flora of oak forests and páramo, we are able to confirm general phytogeographical trends recorded from vascular plant genera of the study area although the latter were more rich in temperate taxa. (2) Andean‐centred species are a conspicuous element in the bryophyte flora of Cordillera de Talamanca, reflecting the close historical connection between the montane bryophyte floras of Costa Rica and South America. (3) High percentages of Central American endemics in the bryophyte flora of the oak forests suggest the importance of climatic changes associated with Pleistocene glaciations for allopatric speciation.